Molecular Methods of Animal Species Identification - Malewski, Tadeusz; Dzikowski, Andrzej; Sołtyszewski, Ireneusz (Polish Journal of Natural Sciences, 2023)
Species identification of animals carried out with molecular biology methods plays an increasingly important role in laboratory practice. Currently, such methods are used, i.e., in phylogenetics, environmental protection, forensic medicine and forensic veterinary medicine, plant and animal breeding. DNA analysis is of particular importance in the identification of protected and endangered animal species being subject to illegal trade. Illicit commerce concerns both live animals and variety of products and objects made of them. In case of such products and objects, identification based on the morphological characteristics is not possible. It is, therefore, necessary to use animal DNA analysis. The paper analyses and presents molecular methods of animal species identification currently in use beginning from qualitative PCR-based methods: random amplification of polymorphic DNA – RAPD-PCR, restriction fragment length polymorphism PCR – RFLP-PCR, single-stranded conformational polymorphism PCR – SSCP-PCR, though quantitative: real-time PCR, high resolution melting PCR – HRM-PCR and finishing DNA barcoding and metabarcoding methods.